Critical Analysis of Bourdieu’s Theory of Distinction with a Metatheory Approach - Tahere Lotfi Khachaki; Ali Yousofi (پژوهش‌نامۀ انتقادی متون و برنامه‌های علوم انسانی)
The present study seeks to introduce and critique Pierre Bourdieu's theory of distinction with a metatheory approach. The distinctive metatheory analysis is based on the four factors of the theoretical and social contexts of the theorist, basic assumptions, content concepts, logical relations of propositions and explanatory processes of theory, and finally a critique of theory based on the views of one of Bourdieu's key critics. The results of the transnational analysis show that Bourdieu's social world is full of unpleasant distribution of position and resources, and this has highlighted the theoretical concern of differentiation. The conflicting influences of Marxist, existentialism, structuralism, and activism have also created an interest in fusion theory in Bourdieu. In combining agency and structure, he considers the agency of individuals in a way that affects both the mind and the structure. He sees society as an interconnected set of fields (structures), capitals, and habitus. In his view, differences in habituation, capital, and position in the field lead to differences and distinctions in lifestyles. However, insufficient attention to the moral aspects of action, ignoring the role of emotions in the process of reasoning and prioritizing interests as the basis for social competition have been considered as the most important criticisms of Bourdieu's theory of distinction.